Inflammatory bowel disease in Turkish children - Cakir, Murat; Unal, Fatih; Dinler, Gonul; Baran, Masallah; Yuksekkaya, Hasan Ali; Tumgor, Gokhan; Kasirga, Erhun; Kalayci, Ayhan Gazi; Aydogdu, Sema (World journal of pediatrics : WJP, 2015)
Background This study was undertaken to evaluate demographics, clinical manifestations, laboratory findings and outcomes of children with inflammatory bowel disease (IBD) in Turkey. Methods We analyzed the medical records of 127 children diagnosed with IBD (under 18 years old) between January 2004 and January 2012 in 8 pediatric gastroenterology centers. Results Of the 127 patients, 90 (70.9%) suffered from ulcerative colitis (UC), 29 (22.8%) from Crohn’s disease (CD), and 8 (6.3%) from IBD unclassified. The mean age of the 127 patients was 11.6±4.1 years, and 11.8% of the patients were below 5 years old. Of the patients, 49.6% were male, and males were more predominant in patients with CD than in those with UC (72.4% vs . 42.2%, P =0.008; a male/female ratio of 2.62 in CD, P =0.0016). Approximately one fifth of the patients had extra-intestinal manifestations and 13.3% of the patients had associated diseases. Extraintestinal manifestations and associated diseases were more common in early onset disease [ P =0.017, odds ratio (OR)=4.02; P =0.03, OR=4.1]. Of the patients, 15% had normal laboratory parameters including anemia, high platelet count, hypoalbuminemia, hypoferritinemia, and high sedimentation rate. Area under receiver operation characteristics was used to predict pancolitis in patients with UC. The values of C-reactive protein, sedimentation rate and pediatric ulcerative colitis activity were 0.61 ( P =0.06), 0.66 ( P =0.01) and 0.76 ( P =0.0001), respectively. Four (4.4%) patients with UC underwent colectomy, and finally two (1.5%, 95% confidence interval: 0-3.7%) patients died from primary disease or complications. Conclusions IBD is an increasing clinical entity in Turkey. Features of IBD are similar to those in other populations, but prospective multicenter studies are needed to analyze the true incidence of IBD in Turkish children.